IECEC 96. Proceedings of the 31st Intersociety Energy Conversion Engineering Conference
DOI: 10.1109/iecec.1996.553876
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-air: status of technology and applications [secondary cells]

Abstract: Over the years, the use of Aluminum as an anode has attracted many potential applications due to its very high theoretical amperehour capacity, voltage and specific energy. In reality, although these values are reduced due to system inefficiencies, this electrochemistry stiU yields energy densities that exceed many other couples. Since the early 1980% Aluminum-Air technology has rapidly advanced to a safe, reliable system that possesses practical energy densities of 300-500 Wh/kg and specific power to 22.6 Wkg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This prevents hydroxide build-up and cathode pore blocking [60], removes hydrogen bubbles from the aluminium surface [61] and allows integration of peripherals such as a heat exchanger or filter/crystalliser unit [15]. A heat exchanger helps to cool down the electrolyte, preventing it from boiling [62], while a crystalliser promotes the crystallisation of Al(OH) 4 À into insoluble Al(OH) 3 , increasing the OH À ion concentration, via reaction (13).…”
Section: Choice Of Electrolyte For Aluminiumeair Cellsmentioning
confidence: 99%
“…This prevents hydroxide build-up and cathode pore blocking [60], removes hydrogen bubbles from the aluminium surface [61] and allows integration of peripherals such as a heat exchanger or filter/crystalliser unit [15]. A heat exchanger helps to cool down the electrolyte, preventing it from boiling [62], while a crystalliser promotes the crystallisation of Al(OH) 4 À into insoluble Al(OH) 3 , increasing the OH À ion concentration, via reaction (13).…”
Section: Choice Of Electrolyte For Aluminiumeair Cellsmentioning
confidence: 99%
“…78 During the 1990"s, a group at Alcan developed a range of alloys containing Sn, Ga, In and/or Mg and described optimum compositions for both alkaline and brine electrolytes. 24,79,80 In saline electrolytes it has been shown that the addition of In 3+ ions in the electrolyte revealed activation of pure Al which increases with increase of In 3+ concentration. 24 In contrast to pure Al, deactivation was observed solutions.…”
Section: Saline Electrolytes: Metal Ions and Al Alloyingmentioning
confidence: 99%
“…While the AB50V alloy developed by Alcan 24,79,80 is an excellent material for high current density dissolution in certain situations, there are two major problems preventing the design of such a battery.…”
Section: Is a High Energy/power Density Al-air Battery Possible?mentioning
confidence: 99%
“…The parasitic chemical reaction occurs between the aluminum anode and the electrolyte and is more severe under alkaline electrolyte conditions. The self-corrosion reaction is harmful to aluminum-air batteries, which will cause battery capacity loss and reduce discharge efficiency [7][8] [9] . Efforts have been made on many fronts to overcome this problem.…”
Section: Introductionmentioning
confidence: 99%